Assessment of soy soluble polysaccharide, gum arabic and OSA-Starch as emulsifiers for mayonnaise-like emulsions. (June 2016) - Chivero, Peter; Gohtani, Shoichi; Yoshii, Hidefumi; Nakamura, Akihiro
Abstract: Hydrocolloid emulsifiers, soy soluble polysaccharide (SSPS), gum arabic (GA), and octenyl succinate starch (OSA-S), were investigated for their ability to produce oil-in-water (O/W) mayonnaise-like emulsions. Xanthan gum (XG) was used as a stabilizer and/or thickener. Oil content above 60%wt. could not be completely emulsified by all three types of emulsifiers. Emulsion separation was observed immediately after preparation. Long term emulsion stability depended on the amount of dispersed phase with higher dispersed phase contents conferring more stability due to a strong network of droplets formed in the system. The formation of Pickering emulsions was confirmed in OSA-S stabilized emulsions. All emulsion systems showed pseudoplastic behavior similar to typical mayonnaise, which increased with an increase in the dispersed phase volume. It was concluded that it is possible to employ hydrocolloid emulsifiers to produce mayonnaise. Highlights: SSPS, gum arabic and OSA starch were used as sole emulsifiers in mayonnaise. 60%wt. and below of oil could be emulsified producing stable emulsions. Emulsion rheograms were fitted into the Power Law and Herschel-Bulkley rheological models.